The Benefits of Modesty: Considering Incremental Professional Development for Mathematics Teachers - Samuel Otten; Zandra de Araujo; Amber G. Candela (Education Sciences)
Professional development (PD) for mathematics teachers often emphasizes transformative instructional change. However, a more modest, incremental approach may offer a higher likelihood of success in ways that complement transformational efforts. This Editorial discusses the potential advantages of incremental PD where teachers make small but meaningful improvements to their practice over time. We explore the differences between transformational PD and incremental PD as evidenced by the articles in this Special Issue. We also distinguish between varieties of incremental PD projects, from those that focus on a small piece of a larger instructional vision (piece-and-support incremental PD), those that set out to achieve a modest goal without appeal to a broader instructional transformation (modest-goal-with-support incremental PD), to a more radically modest approach that involves offering small, optional instructional suggestions without investments of time or training (nudge-based incremental PD). Ultimately, this Editorial, and this Special Issue as a whole, advocates for new conversations and investigations into how PD is structured and how the promoted instructional changes might spread among mathematics teachers.